A Western Case of Intravascular Large B-Cell Lymphoma as Unusual Cause of Persistent Fever - Pier Paolo Piccaluga; Stefania Paolini; Cristina Campidelli; Nicola Vianelli; Luigi Bolondi (Case Reports in Hematology)
Fever of unknown origin (FUO) is a common and challenging clinical condition that can be referred, among others, to infections, drug’s effects, various inflammatory disorders, and cancers. Among the latter, lymphomas can indeed cause fever, which is therefore accounted as a lymphoma-related sign in patients’ staging. Intravascular large B-cell lymphoma (IVLBCL) is a very rare tumor, characterized by lymphoma cell accumulation within sinusoids and, despite a very aggressive course, the evidence of this disease is scarce. Two variants are currently recognized, respectively, occurring in either Western (mainly characterized by neurological symptoms and skin involvement) or Eastern countries (with hemophagocytic syndrome, bone marrow, spleen, and liver involvement). We describe an atypical and unprecedented IVLBCL patient, presenting with pronounced features of Eastern cases as well as skin involvement. Due to the scant amount of neoplastic cells, the diagnosis was very challenging, with FUO being the first and for a certain time unique clinical sign. Although lymphoma was suspected, the lack of evidence for neoplastic cells delayed the final diagnosis. Eventually, only autopsy revealed the extensive involvement of different organs and tissues.